2022
DOI: 10.3390/atmos13071074
|View full text |Cite
|
Sign up to set email alerts
|

Probability Forecasting of Short-Term Short-Duration Heavy Rainfall Combining Ingredients-Based Methodology and Fuzzy Logic Approach

Abstract: Highly convection-related short-duration heavy rainfall (SDHR), defined as rainfall greater than 20 mm h−1 of a whole hour, causes severe damage every year in China. An objective forecasting method is developed to provide guidance products for the short-term probability of SDHR. Representative parameters of environmental moisture content, instability, and dynamical forcing are selected as predictors based on the ingredients-based methodology. The predictors are selected by comparing their ability to discrimina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…It is found that specific humidity at 850 hPa with higher weights could lead to a slight increase of the highest TS. Besides, the indicators representing atmospheric environmental conditions are important for probability forecasting (Tian et al, 2022). In this study, we make an attempt to forecast the probability of SDHR occurrence induced by NCCV based on limited environmental parameters, more work should be carried out to improve the forecast capability for SDHR caused by NCCV in the future.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It is found that specific humidity at 850 hPa with higher weights could lead to a slight increase of the highest TS. Besides, the indicators representing atmospheric environmental conditions are important for probability forecasting (Tian et al, 2022). In this study, we make an attempt to forecast the probability of SDHR occurrence induced by NCCV based on limited environmental parameters, more work should be carried out to improve the forecast capability for SDHR caused by NCCV in the future.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…In order to verify the indicators of the above environmental parameters for SDHR, we quantitatively select some representative parameters to make probability forecasting for SDHR caused by NCCV (Tian et al, 2022). The overlapping size of the relative frequencies of SDHR and ordinary precipitation (S1) and SDHR and non-precipitation (S2) are calculated for the above parameters (Table 1).…”
Section: Probability Forecastingmentioning
confidence: 99%
See 3 more Smart Citations